Economic Growth Analysis of Lampung Province: A Review of Open Unemployment Rate, Inflation, and Investment during the 2013–2023 - Asrul, Mutiarani; Mustofa, Ulul Azmi; Yunarti, Yuyun (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
From 2013 to 2023, this quantitative research evaluates how inflation, unemployment, and investment effect Lampung Province economic growth. SPSS version 27 and multiple linear regression analysis were used to examine how the three independent variables affected regional economic performance using secondary annual Central Bureau of Statistics data. Testing for normality and heteroscedasticity confirmed the model. Inflation, unemployment, and investment statistically hurt Lampung's economy. These variables explain 86.2% of regional economic growth, proving their potency. Regional economic development requires purposeful governmental initiatives, according to the results. Stabilizing inflation, boosting investment quality—especially in the productive real sector—and raising employment are needed for long-term development. According to the paper, local governments should address economic issues using evidence-based economic planning. It also shows regional growth patterns' complexity beyond inflation, unemployment, and investment. To broaden these findings, future research should examine infrastructure, education, and institutional support. These characteristics may help us understand economic growth's multiple causes and develop context-specific policies. This study gives Lampung Province policymakers empirical data on regional development.